Design of Dual-Band, 4-Ports MIMO Antenna-Diplexer Based on Quarter-Mode Substrate Integrated Waveguide - Mansour H. Almalki; Adnan Affandi; Avez Syed (International Journal of Antennas and Propagation)
Here, a compact, dual band, 4-elements multi-input and multi-output (MIMO) antenna diplexer is designed to use in wireless local area network (WLAN) applications. The antenna is accomplished in a planar profile by employing Substrate Integrated Waveguide (SIW) technology. To reduce the size of a single element by 75%, a quarter-mode substrate integrated waveguide (QMSIW) technology is introduced. The QMSIW is realized by bisecting the full-mode SIW along the two magnetic walls and considering the quarter-mode for the operation. Initially, two-QMSIW cavities of distinct dimensions are designed to operate in two frequency bands, 5.2 GHz and 5.8 GHz, respectively. Later, two more radiating elements operating at the same frequencies are integrated with a 2-elements antenna. For better polarization decoupling, the identical elements are placed perpendicular to each other, and a parasitic metallic strip loaded with shorting vias is placed between two identical frequency antenna elements; hence, the port isolation is improved up to −25 dB. The antenna covers a bandwidth of 1.8% in the lower frequency band while 2.2% in the upper frequency band. The antenna prototype is fabricated, and its results are verified with experimental data. It is observed that the measured results are closely following the simulated results.